Parâmetros morfofuncionais e sensóriomotores: um estudo com atletas de taekwondo e universitários - SILVA, Thase Marcielle Rodrigues da (2022)
Studies have shown that both morphofunctional and sensorimotor parameters are related to the good performance of taekwondo practitioners (TKD). Thus , the aim of this study was to identify, compare and analyze the main morphofunctional and sensorimotor characteristics in athletes of TKD and students to verify if there are significant differences between these groups. The sample consisted of 15 male individuals who were divided into two groups: (n = 7) Taekwondo ( 28.57 ± 7.23 years old ) and (n = 8) Control Group, composed of university students ( 23, 12 ± 4.42 years old). From the inclusion criteria, only taekwondo athletes, graduated in the black belt, were part of this study. The control group, on the other hand, was composed only of university students who did not practice any martial art. All subjects were submitted to body mass measurement, height, BMI, combined with motor tests of thoracolumbar flexibility and scapular force. To verify the effectiveness of sensorimotor processes, the Response Time (TR) test was applied using the TReaction application . The results demonstrate that there are no significant differences in the morphofunctional parameters (body mass, height, BMI and age) of these groups. However, the subjects presented significant differences in flexibility [t (13 ) = 2.583, p = 0.023] and TR [ t (13) = -2.904, p = 0.0012]. It is concluded that there is significant improvement in the level of neural system in athletes and taekwondo practitioners, this improvement is directly linked to faster response time, a person takes to respond satisfactorily to a certain stimulus received, be it visual or audible. It has also been found that the components of physical fitness strength and flexibility are better in TKD practitioners.